Feature extraction based on mel-scaled wavelet packet transform for the diagnosis of voice disorders - Murugesa Pandian, Paulraj, Prof. Madya Dr; Sazali, Yaacob, Prof. Dr.; Muthusamy, Hariharan, Dr. (SpringerLink, 2011)
Link to publisher's homepage at http://springerlink.com/